NATO’S INVOLVEMENT IN HUMANITARIAN OPERATIONS/DISASTER RESPONSE - Jacuch Andrzej (2020)
The article analyses NATO’s role in humanitarian aid and disaster relief operations. It presents NATO structures, tools and examples of operations coordinated by NATO. It underlines the added value offered by NATO in the environment and in relation to other major humanitarian actors such as the United Nations and the European Union.